Combination of pregnancy and breast cancer - A. L. Chernyshova; A. A. Chernyakov; E. Yu. Garbukov; N. A. Tarabanovskaya; Yu. M. Trushchuk; O. S. Dil; S. E. Krasilnikov; A. V. Shumeykina (Опухоли женской репродуктивной системы, 2023)
Breast cancer (BC) occupies the second place in terms of incidence and the first ranking place in terms of mortality among oncopathology in women. The article presents the current state of the problem of the combination of BC and pregnancy, the impact of pregnancy on the course and outcome of breast oncopathology, as well as modern hypotheses for the development of breast cancer during pregnancy. It is shown that the current studies are quite contradictory and in many ways not accurate enough in methodology and materials. We present a clinical case of BC associated with pregnancy. The case is interesting from 2 positions: on the one hand, the patient’s tumor process is associated with pregnancy, on the other hand, there is a very rare combination of HER2/neu- and BRCA1-positive status.According to the presented literature data and our own data, it was concluded that the treatment of patients with BC during pregnancy is a difficult task and is often accompanied by tumor progression, despite the standard treatment regimens. Undoubtedly, this group of patients needs to develop new methodological approaches to antitumor treatment based on a deep analysis of the molecular genetic characteristics of the tumor, the hormonal background in general, and its effect on the tumor process during pregnancy. Such a personalized approach will improve the results of treatment of young patients with BC during pregnancy.